2013
DOI: 10.5935/abc.20130088
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Risk Scores with Coronary Anatomy in Non-ST-elevation Acute Coronary Syndrome

Abstract: Risk scores correlate with the severity of coronary lesions, and the TIMI risk score showed the best predictive ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Ischemic heart disease is a leading cause of death worldwide and acute coronary ischemia is responsible for the largest number (Santos et al, 2013). Elevated circulating LDL levels increase risk for ischemic cerebro-and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic heart disease is a leading cause of death worldwide and acute coronary ischemia is responsible for the largest number (Santos et al, 2013). Elevated circulating LDL levels increase risk for ischemic cerebro-and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…7 The risk stratification is important as it has been consistently proved that early coronary intervention in high-risk patients improves clinical outcomes. The main focus of this strategy is to evaluate the probability of occurrence of adverse events, analyzing data from the clinical history, physical examination, ECG findings and cardiac biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relationship between TRS and the severity of CAD has been shown in several studies. TRS was compared with the results of coronary angiography in 683 patients with NSTE-ACS; for each increased risk category, the 3-vessel disease was shown to be more frequent (1). In the PRISM-PLUS study of 1491 patients with ACS, it was shown that there were more severe coronary lesions and left main coronary lesions in patients with high TRS compared with those with low TRS (45).…”
Section: Reflow No-reflow P Valuementioning
confidence: 99%
“…This index has been shown to be useful and helpful in many studies (15,16). Many studies have investigated the relationship between GRS, TRI, and ACS (1,(17)(18)(19), but none have addressed the association between TRI, TRS, GRS, and NRF in patients with STEMI. We investigated whether preintervention TRI, TRS, and GRS are related to coronary NRF in patients with STEMI who underwent primary percutaneous coronary intervention (p-PCI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation